Abdominal mycobacterial infection in acquired immunodeficiency syndrome patients - Guidugli, Ruggero Bernardo; Siqueira, Sheila Aparecida Coelho; Senise, Jorge de Figueiredo; Silva, Anderson José da; Hamrick, Paul; Figueiroa, Nancy Rezende (São Paulo Medical Journal, 1995)
The authors studied 12 patients with AIDS and abdominal mycobacteriosis hospitalized in the Hospital Ipiranga (São Paulo, Brazil), from June 1989 to January 1992. Diagnosis was confirmed by the histopathological examination of organ specimens collected during laparotomy, which, in most cases, was carried out due to an emergency situation. Observations included perforation of the ileum, seropurulent fluid involved and bloked by viscera, epiploon, and fibrin. Hepatoesplenomegaly was present in all patients and generalized granulomatous peritonitis was observed in more than 50%. A patient died in the immediate post-op period, four after an average period of 55 days in the hospital. A patient evolved with stercoral fistula and asked to be discharged. Six patients were discharged after an average hospitalization period of 27 days. The authors stress that in developing regions where tuberculosis incidence is high, a patient with AIDS and a painful and irritative abdominal picture should always lead to the hypothesis of mycobacteriosis.